Constraints and Determinants of Coffee Processing Methods in Gulmi District, Nepal - Paudel, Manoj; Parajuli, Kiran (International Journal of Applied Sciences and Biotechnology, 2020)
Nepalese coffee is widely recognized as organic and specialty coffee due to its peculiar aroma and flavor. Altitude, geographical location, orchard management practices, post-harvest handling are the major factors that affect the coffee quality. Coffee quality is determined 40% in the field, 40% at post-harvest primary processing, and 20% at secondary processing. In Nepal, dry and wet methods are the most common coffee processing methods. Wet processed coffee is more preferred by the consumers in comparison to dry coffee and commands higher price. Main objective of the study was to know the most common processing method adopted in Gulmi district and to know the determinants and constraints of the processing method. 100 coffee growers from four different local bodies of Gulmi district were selected by the purposive sampling method for the household survey. Descriptive statistics, logit model and index score ranking method were used for the data analysis. Gender of household head (p <0.01), education level (p<0.05) and technical trainings (p<0.05) were found to have significant effect upon the selection of processing methods. Due to several constraints all coffee growers were unable to adopt wet processing of coffee. Index score method was used to rank the constraints for adoption of wet processing methods. Lack of availability of hand pulpers was ranked as the major constraint by the coffee growers with an index score of 0.867 followed by unavailability of water, no access to transportation as other major constraints for adoption of wet processing method. Int. J. Appl. Sci. Biotechnol. Vol 8(3): 368-373